Inhibition of Reticulocyte Peptide-Chain Initiation by Pactamycin: Accumulation of Inactive Ribosomal Initiation Complexes - Kappen, Lizzy S. (1973)
Pactamycin does not inhibit the overall initiation factor- and GTP-dependent binding of [(35)S]Met-tRNA(f) to rabbit reticulocyte ribosomes but does prevent the formation of Met-puromycin, provided that the antibiotic is present during the course of the binding reaction. These data indicate that pactamycin blocks the synthesis of a functional peptide-chain initiation complex. Sucrose density gradient centrifugation analysis of binding reactions shows that pactamycin causes the accumulation of an initiation complex on the smaller ribosomal subunit (smaller initiation complex), to which the 60S ribosomal subunit either cannot join or with which it forms a larger inactive 80S initiation complex that falls apart under the conditions used for isolation. The smaller initiation complex formed in the presence of pactamycin differs from the normal intermediate in peptide-chain initiation in being much more resistant to degradation by pancreatic RNase. In the presence of pactamycin, the inactive smaller complex can also form on mRNA to which an unaffected ribosomal couple is already attached, forming an oligoribosome lacking a larger ribosomal subunit or a “1.5 mer.” These effects of pactamycin can be overcome to a considerable degree by elevation of the Mg(2+) concentration.